2017
DOI: 10.1002/mp.12560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vessel enhancement algorithms applied to time‐of‐flight MRA images for cerebrovascular segmentation

Abstract: Vessel enhancement algorithms can help to improve the accuracy of the segmentation of the vascular system. However, their contribution to accuracy has to be evaluated as it depends on the specific applications, and in some cases it can lead to a reduction of the overall accuracy. No specific filter was suitable for all tested scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…These values are then used to determine the standard deviation values for the Frangi filter (Shikata et al, 2004). The minimum sigma value (0.8) and the increment in sigma (0.2) were chosen based on prior literature (Phellan and Forkert, 2017). The maximum sigma values were then selected based on the relation sigma max = √ radii max (Krissian et al, 2000).…”
Section: Mip Vessel Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are then used to determine the standard deviation values for the Frangi filter (Shikata et al, 2004). The minimum sigma value (0.8) and the increment in sigma (0.2) were chosen based on prior literature (Phellan and Forkert, 2017). The maximum sigma values were then selected based on the relation sigma max = √ radii max (Krissian et al, 2000).…”
Section: Mip Vessel Segmentationmentioning
confidence: 99%
“…While existing methods are limited to applying vessel enhancement filters to either the original non-projected 3D images or a single MIP through the entire imaged volume (Gao et al, 2011;Hsu et al, 2017;Phellan and Forkert, 2017), there has been little investigation of the influence of projection thickness on the effectiveness of vessel segmentation. Of the few studies reported, one showed similarity between vessel radii measurements extracted from parameter-dependent MIP MRA and digital subtraction angiography derived from high contrast x-ray images (Persson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include prior segmentation of the TOF and/or ASL dataset to enhance the vessel-to-background contrast, centerline and bifurcation prediction of the vessels, automated detection of impaired flow behavior (e.g. in stenosis) and risk of rupture in aneurysms [20][21][22][23][24]. Additionally, databases of normal vascular images as well as normal flow behavior can be used to early detect pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…The labeled image is then subtracted from the control image to remove the signal of non-vascular tissues, but some residual noise can still be observed, even after subtraction, particularly in the last images of the 4D ASL MRA sequence. As a last preprocessing step, the subtracted images are filtered using the multiscale vesselness filter designed by Erdt et al [21], which enhances the intensity of vessels in the images and has been shown to help to increase the accuracy of the final segmentation [22].…”
Section: A Segmentationmentioning
confidence: 99%